Streptomyces spp. as plant growth promotors and regulators of Eucalyptus under heat, drought and saline stress and genome insights into three selected strains - Kaewkla, Onuma; Kiakhunthod, Kawintip; Chookhampaeng, Sumalee; Chutiman, Nipaporn; Klankeo, Piriya; Pachanakarn, Napaporn; Franco, Christopher Milton Mathew (Frontiers in Agronomy, 2025)
This is the first report of the application of six endophytic actinobacteria, isolated from eucalyptus trees growing in a saline soil, to test their effects on eucalyptus growth. This study aims to examine six selected strains to promote eucalyptus growth under drought, heat, and salinity conditions. Genomes of the three selected strains were analyzed to reveal significant genetic traits that may contribute to stress tolerance in eucalyptus. Eucalyptus seeds soaked with spores of each of the six actinobacteria were grown hydroponically for 41 days with natural heat wave conditions. Strain A2 gave the highest shoot and root length, plant fresh (PF) weight, and number of lateral roots, which were significantly higher than the control. Strain A3 gave the highest chlorophyll a (Ch a) and chlorophyll b (Ch b), and plant dry weight and leaf area were significantly higher than the control. Furthermore, the six actinobacterial strains were tested for seedling length vigor index (SLVI) at 0, 50, 100, 150, and 200 mM NaCl, and the result indicated that strain A5 was the best, having the highest SLVI at 200 mM NaCl. Strains A2, A3, and A5 were selected to test plant growth promoting (PGP) activity in eucalyptus cuttings under three different conditions: drought, limited water with heat stress (less than 40°C), and heat stress (40-42°C). Strains A2, A3, and A5 showed a negative impact on cuttings with a stress severity index (SSI) higher than the control in drought and heat stress (40-42°C). Strains A3 and A5 showed lower SSI than the control and strain A2 in limited water with heat stress (38-39°C). Insights into three genomes of strains A2, A3, and A5 reveal biosynthetic gene clusters (BGCs) of antimicrobial compounds, ectoine, and siderophore production, including genes related to stress response. In conclusion, strain A3 exhibited a negative effect on plant growth in some circumstances, which means this strain is not suitable to use as a PGP in future applications. Endophytic actinobacteria strains A2 and A5 could support plant growth in hydroponic and saline conditions, and these selected strains could be used as inocula for eucalyptus plantations in the future.